2015
DOI: 10.1590/2177-6709.20.6.075-081.oar
|View full text |Cite
|
Sign up to set email alerts
|

Malocclusion prevalence and orthodontic treatment need in central Anatolian adolescents compared to European and other nations' adolescents

Abstract: Objective: To determine the prevalence of malocclusion and orthodontic treatment need in a large sample of Central Anatolian adolescents and compare them with European-other nations' adolescents. Methods: The sample included 1125 boys and 1204 girls aged between 12 and 16 years with no previous orthodontic treatment history. Occlusal variables examined were molar relationship, overjet, overbite, crowding, midline diastema, posterior crossbite, and scissors bite. The dental health (DHC) and aesthetic components… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
49
6
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(70 citation statements)
references
References 23 publications
5
49
6
4
Order By: Relevance
“…In our study, according to Angle's classification, 55.1% of children had class 1 malocclusion; this result was similar to that of a study performed with 100 children (10-12 years of age) in Turkey (21). However, recent studies have shown that the most common malocclusion in adolescents is class 2 malocclusion in Turkey (22)(23)(24)(25). Nevertheless, when the literature review was done, data on the prevalence of malocclusion are limited (26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, according to Angle's classification, 55.1% of children had class 1 malocclusion; this result was similar to that of a study performed with 100 children (10-12 years of age) in Turkey (21). However, recent studies have shown that the most common malocclusion in adolescents is class 2 malocclusion in Turkey (22)(23)(24)(25). Nevertheless, when the literature review was done, data on the prevalence of malocclusion are limited (26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…Malocclusions are the third most prevalent alterations with the third greatest psychosocial impact (9) . According to Bilgic (2014), almost a third of the population evaluated have a very great need of orthodontic treatment (10) . In addition, a study conducted in Chile found that 96.2% of students examined had some kind of malocclusion (9) .…”
Section: Introductionmentioning
confidence: 99%
“…Las ADM constituyen un problema de salud pública ya que junto a caries y enfermedades gingivales/periodontales son las patologías orales más prevalentes tanto en Chile como en el resto del mundo (Bellot-Arcis et al, 2012;Bilgic et al, 2015). Los estudios realizados en nuestro país entregan prevalencias de ADM de 32,4 % en niños y 60 % en adolescentes a nivel regional (Bellot-Arcis et al).…”
Section: Introductionunclassified
“…La etiología es multifactorial, existiendo predisponentes de carácter sistémico, hereditario y congénito. También existen factores locales tales como pérdida prematura de dientes temporales por trauma o caries, restauraciones inadecuadas, malos hábitos y otros (Ahsan et al, 2013).Las ADM constituyen un problema de salud pública ya que junto a caries y enfermedades gingivales/periodontales son las patologías orales más prevalentes tanto en Chile como en el resto del mundo (Bellot-Arcis et al, 2012;Bilgic et al, 2015). Los estudios realizados en nuestro país entregan prevalencias de ADM de 32,4 % en niños y 60 % en adolescentes a nivel regional (Bellot-Arcis et al).…”
unclassified